(untitled) (Editora Impacto Científico, 2025)
Although it is a fundamental science for areas such as medicine and industry, the teaching of Chemistry is still dominated by a traditional model centered on the memorization of formulas, rules, and nomenclature, generally without connection to the social reality of the students. Working with the 1st year class of the technical course in Roads at the Federal Institute of Alagoas - Maceió Campus, it was found that many students viewed Chemistry as something abstract. Therefore, the PIBID scholarship holders intervened, with the support of the supervising teacher, introducing experimental practices for the production of cleaning products and corroborating the classes with the subjects of stoichiometry, inorganic functions, and chemical bonds. The analysis of the students’ reports revealed that the experimental practices favored the conceptual, functional, and integrated appropriation of chemical content, frequently addressed in an abstract way in high school. DOI: https://doi.org/10.56238/edimpacto2025.090-089